PENGARUH BIAYA PRODUKSI TERHADAP PENJUALAN PADA PT. PT SHINDENGEN INDONESIA - Hartanti Hartanti (Universitas Bina Sarana Informatika, 2016)
Sales is the main thing in the company, because the main source of income comes from the sale. This study aimed to determine the effect of the cost of production to sales at PT. Shindengen Indonesia. This study used quantitative analysis techniques, which are becoming variable x is a variable y, while production costs are the result of the sale. Data in the form of time series data is data production costs and sales results from January 2013 to December 2015.Penulis using correlation analysis, regression and determination, and the data were processed using SPSS version 21. The results showed that there is a very strong relationship of 0.998 between production costs with sales and coefficient of determination shows R Square of 99.6% where the results of sales at PT Shindengen Indonesia affected by the cost of production amounted to 99.6%, remaining at 0.4% influenced by other variables that are not analyzed in this study. Based on hypothesis testing by t test obtained t count> t table (87 945> 2.032), then Ho is rejected, it means that there are significant effect between production costs with sales results. To suppress the increase in production costs as a result of failure cost PT Shindengen Indonesia should provide guidance to employees to keep concentration at work and always adhere to the intruction work or work instructions so as to reduce production costs and profits can be increased. Key words: Costs of production, sales